PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MILENIAL DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA BANK MUAMALAT KC YOGYAKARTA) - Nina Victuria; Farid Hidayat (Program Studi Manajemen Fakultas Ekonomi UST, 2022)
This study aims to analyze the ef ect of leadership style and compensation on the performance of millennial employees with motivation as an intervening variable (a case study on employees of Bank Muamalat KC Yogyakarta). This study uses a quantitative approach with sampling using purposive sampling method. The data collection technique used a questionnaire with a total sample of 30 respondents. The analytical tool used is path analysis with the help of the IBM SPSS Statistic 24 data analysis tool The results showed that the variables of leadership style, compensation and motivation simultaneously af ect employee performance. The variables of leadership style and compensation simultaneously have an ef ect on motivation. Partially, leadership style and compensation variables have no ef ect on employee performance. While the motivation variable has a significant positive ef ect on employee performance. The leadership style variable has a significant positive ef ect on motivation. While the compensation variable has no ef ect on motivation. Motivational variables can mediate leadership style and compensation variables on the performance of millennial employees.